A facile strategy for enhancing tensile toughness of poly(lactic acid) (PLA) by blending of a cellulose bio-toughener bearing a highly branched polycaprolactone. (15th July 2022) - Zafar, Roshaan; Lee, Woojin; Kwak, Seung-Yeop
Graphical abstract: The cellulose graft copolymer bearing a highly branched poly(ε-caprolactone) structure, upon blending with PLA induces an more ordered crystal phase resulted in significantly enhanced toughness of PLA bio-blends. Highlights: A series of PLA/cellulose graft copolymer (CghbP) bio-blends were fabricated. The prepared PLA/CghbP blend series were found to be miscible at scale of 10–30 nm. An optimal loading of CghbP induced a structurally robust PLA-based bio-blend. The enhanced toughness was related to a hard/soft multi-phase system of PLA blend. The prepared PLA/CghbP exhibited excellent migration stability and bio-degradability. Abstract: In this research, a series of PLA bio-blends with a highly-branched polycaprolactone (PCL)-grafted cellulose bio-toughener (CghbP) (i.e., PLA/CghbP series) were facilely fabricated and characterized to improve the tensile toughness of neat PLA. The prepared PLA/CghbP bio-blends were examined by attenuated total reflection Fourier-transform infrared (ATR FT-IR) spectroscopy and differential scanning calorimetry (DSC) analysis to be physically intact and partially miscible at the scale of ca.10∼30 nm. It was confirmed by the DSC and wide-angle X-ray diffraction (WXRD) analyses that the incorporation of CghbP into PLA matrix can induce a more disordered α′ crystalline phase of PLA in the prepared PLA/CghbP blends. The tensile properties of PLA/CghbP bio-blends investigated by universal testing machine (UTM) suggested that the mechanical behavior of highly-tough hard/soft multiphase polymeric system was realized with the incorporation of 5 wt% CghbP to PLA (i.e., PLA/CghbP5), resulting in a ∼215% increase in the tensile toughness (56.1 MJ m −3 ) compared to pristine PLA (17.8 MJ m −3 ). This research empirically identified that the improved tensile toughness of PLA/CghbP bearing 5 wt% CghbP are conjunctly correlated with the concurrent formation of more ordered hard PLA α crystalline and highly-branched soft phase induced by the loading of an appropriate CghbP into PLA. Furthermore, the PLA/CghbP5 bio-blend showed remarkably higher migration stability with the weight loss ∼0.1% CghbP after additive spillage test than those of other PLA/CghbP blends and PLA blends with conventional low molar mass plasticizers.